Myth and paradox in Aristophanes: The poetics of appropriation - Kanellakis, D (Crete University Press, 2018)
Offering a close reading on the most elaborate and paradoxical reworkings of mythical material by Aristophanes in his extant plays, this paper sheds light on the poetics of this procedure: what is changed, how, and why. Special emphasis is placed upon the poetological intention of appropriation, which is to claim the superiority of comedy over other genres. As for their intra-dramatic function (how they operate within the plot), the appropriated myths can be grouped into five categories: ‘persuasive’, ‘aetiological’, ‘antiphonal’, ‘abusive’, and ‘structural’ myths.